An Overview of Food Emulsions: Description, Classification and Recent Potential Applications - Meltem Serdaroğlu; Burcu Öztürk; Ayşe Kara (Turkish Journal of Agriculture: Food Science and Technology)
Emulsions take place partially or completely in the structures of many natural and processed foods or some foods are already emulsified in certain stages of production. In general “emulsion” is described as a structure created through the dispersion of one of two immiscible liquids within the other one in form of little droplets. Many terms are available to describe different emulsion types and it is very important to define and clarify these terms like “macro emulsion”, “nanoemulsion” and “multiple emulsion”. Nanoemulsions become increasingly important in food industry as an innovative approach in carrying functional agents. Application potential of multiple emulsions (W/O/W) is also stated to be very high in food industry. The two main strategic purposes of utilization of multiple emulsions in food applications are to encapsulate various aromas, bioactive compounds or sensitive food compounds and to allow the production of the low-fat products. This review provides an overview to the general terms of emulsion types, the role of various emulsifying agents, and the application potential of emulsions in food industry.